Challenges of Financing Infrastructure Deficits Through PPPs : Lessons from Global Experience - Malik, Sakshi; Kaur, Simrit (Indian Journal of Finance, 2020)
Public – private partnerships (PPPs) are increasingly being used globally to bridge infrastructure gaps. PPPs leverage private finances with public funds, thereby meeting infrastructure requirements of countries. PPPs also provide advantages of improved service quality and proper risk management. However, literature posits that PPPs are characterized by the presence of an array of challenges, making such projects vulnerable to distresses and/or cancellations. For instance, during the period from 2005–2018, 76 projects were declared cancelled/distressed, out of which 17 projects were in India alone, that too in a single year, that is, 2012. Against this backdrop, the objective of the present study was to identify the critical challenges pertaining to the lifecycle of PPP projects to enable policymakers formulate policies which minimize the risk of distress in PPP projects. The research methodology adopted was to rely on multiple case studies of PPP projects that had experienced challenges across the three phases of their project life cycle. Phase-1 of the cycle, known as the project development phase, was prone to challenges such as insufficient bids, inadequate competition, and poor feasibility analysis. Select challenges arising in Phase-2, the construction phase, were land acquisition, delays, and cost overruns. Finally, in Phase-3, which corresponded to the operational phase, challenges such as market demand risk and lower than expected revenues existed. Primarily relying on PPP projects in the transport sector, case studies were selected from countries such as India, Ghana, and Australia. Based on the enriching analysis from 12 such case studies, the paper concluded by providing a broad policy perspective.